Efficacy of a Mobile Behavioral Intervention for Workers With Insomnia. Issue 3 (March 2020) - Omeogu, Chinyere; Shofer, Frances; Gehrman, Philip; Green-McKenzie, Judith
Abstract : Objective: Insomnia is often unrecognized in the workplace despite a 10% prevalence. Cognitive behavioral therapy for insomnia (CBTi) is efficacious but often not available. This study assessed the efficacy of the self-guided CBTi Coach mobile app. Methods: Using a pre/post design, the CBTi Coach was evaluated prospectively in hospital nurses with insomnia. The primary outcome measured was the Insomnia Severity Index (ISI) at 0, 3, and 6 weeks. Results: Thirteen of 17 (76%) female nurses who worked day shifts completed the study. Baseline ISI was 18.1 (range 15 to 22). After 3 and 6 weeks, ISI significantly decreased to 12 and 11, respectively. No difference in ISI score was noted between weeks 3 and 6. Conclusion: Use of CBTI Coach app demonstrated significant improvement in sleep quality in nurses with insomnia without coaching or healthcare provider visits.